Religious freedom, minorities and Islam: an inquiry into the Malaysian experience, 2nd. ed. - Yousif, Ahmed F (IIUM Press, 2011)
The 2nd edition of Religious Freedom, Minorities, and Islam: An Inquiry into Malaysian Experience challenges the argument that religious freedom model can only be guaranteed by a separation between religion and state. Additionally, the book tries to show that while an increased religious consciousness and manifest adherence to one’s faith may lead to conflict in a multi-religious society, this hypothesis is not necessarily accurate. Malaysia has been selected as a case study due to its religious, racial, and linguistic pluralism, to analyse the extent to which its religious minorities have the freedom to profess and practice their faith. The degree to which Malaysia exemplifies the spirit of Islamic tolerance toward religious minority groups will also be appraised. Finally, the learned author examines the impact of the growing “Islamic revivalism” on the religious freedom of non-Muslim minorities in Malaysia.